Rare case of rectal perforation by an intrauterine device: Case report and review of the literature. (October 2022) - Boushehry, Reem; Al-Taweel, Talal; Bandar, Asya; Hasan, Maryam; Atnuos, Mario; Alkhamis, Ahmed
Abstract: Introduction and importance: Intrauterine devices (IUDs) are safe, highly effective and reversible forms of contraception. Reliance on IUD has been increasing and as such, it is the responsibility of the healthcare provider to be aware of the complications associated with it. IUD rectal migration is one of the rare but serious complications that may lead to detrimental sequelae. Case presentation: A 30-year-old asymptomatic woman presented to the gynaecology clinic two months after a difficult insertion of an IUD. On examination, the device was not localised in utero with transvaginal sonography. Computed tomography scan and colonoscopy revealed the position of the IUD within the rectum. It was successfully retrieved with a combined laparoscopic-colonoscopic approach. Follow-up flexible sigmoidoscopy showed a well-healed rectal wall. Clinical discussion: IUD perforation can increase the risk of morbidity and necessitates early surgical intervention even if the patient is asymptomatic. Combined laparoscopic-colonoscopic approach allows for safe retrieval of IUD that has perforated the intraperitoneal rectal segment or is firmly embedded within the mucosa. Recognising the risk factors and adhering to the principles of IUD insertion could significantly lower the risk of perforation. Conclusion: This case report highlights the importance of a physician's vigilance regarding a perforating IUD in a patient with a history of a difficult insertion. It is imperative to undertake additional steps to rule out such a complication in these cases. Uterine perforation can be avoided with implementation of safe IUD insertion practice. Highlights: Rates of IUD usage are increasing worldwide. Rectal perforation is a rare complication of IUD insertion. A bimodal approach may be considered for the retrieval of a rectal perforating IUD. Suspect uterine perforation in patients with a history of difficult IUD insertion.